Spinal Tuberculosis within the Vertebral Arch Mimicking a Malignant Tumor: Case Report - Niedermeyer, Sebastian; Draenert, Rika; Beck, Alexander; Todorova, Rumyana; Jung, Andreas; Biczok, Anna-Maria; Tonn, Jörg-Christian; Thorsteinsdottir, Jun (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2022)
Background Spinal tuberculosis is a manifestation of extrapulmonary tuberculosis. The incidence of tuberculosis is low in high-income countries; however, globally, it still remains one of the most frequent fatal infectious diseases. Because of its rarity in developed countries, spinal tuberculosis can be mistaken for malignant tumors of the spine, especially in case of an atypical radiologic manifestation and without pulmonary affection.Methods We present the case of a 39-year-old man from South India with quickly progressing gait disturbance and hypesthesia below the Th10 level. Magnetic resonance imaging revealed an osteolytic lesion of the vertebral arch Th2 with central necrosis and compression of the spinal cord altogether highly suspicious for spinal metastasis.Results After surgical removal of the mass by laminectomy, the patient regained normal neurologic function. Histology revealed a severe granulomatous inflammation and DNAhybridization of polymerase chain reaction (PCR) products detected Mycobacterium tuberculosis-specific DNA in the sample. Biopsy of an enlarged hilar lymphnode allowed us to obtain material to successfully perform a drug resistance test to start specific antimicrobial therapy.Conclusion Spinal tuberculosis, even with atypical radiologic appearance, has to be considered a differential diagnosis in patients with provenance from endemic countries. A multidisciplinary diagnostic approach helps perform antimicrobial susceptibility testing to avoid delaying the start of antibiotic therapy.
Keywords: spinal tuberculosis; spinal tumors; Pott's disease; Mycobacterium tuberculosis